PATHOPHYSIOLOGY OF CHRONIC KIDNEY DISEASE: MECHANISMS AND CLINICAL IMPLICATIONS (Web of Teachers: Inderscience Research, 2025)
Chronic Kidney Disease (CKD) is a progressive condition characterized by irreversible loss of kidney function over time. It represents a major global health problem due to its increasing prevalence and association with high morbidity and mortality. The pathophysiology of CKD involves complex interactions between hemodynamic changes, inflammation, fibrosis, and metabolic disturbances. This article reviews the key pathophysiological mechanisms underlying CKD progression and highlights their clinical significance.